Faktor yang berhubungan dengan kadar hemoglobin ibu hamil: studi kasus kontrol di Puskesmas Pitu Kabupaten Ngawi - Pibriyanti, Kartika; Marfu'ah, Hanan; Luthfiya, Lulu'; Fathimah, Fathimah; Mufidah, Indahtul; Rahayu, Try; Romadhoni, Zhazha Pratiwi; Yuliana, Fitri (Jurnal Gizi Klinik Indonesia, 2025)
Factors related to hemoglobin levels among pregnant women: case control study at the Pitu District Health Center, Ngawi RegencyBackground: Hemoglobin is an indicator of iron availability in the body, and its levels can be affected by iron deficiency. A decrease in hemoglobin levels can lead to anemia, which increases the risk of maternal mortality during childbirth.Objective: This study aimed to analyze factors related to hemoglobin levels, such as nutritional status and Eating patterns, among pregnant women at the Pitu District Health Center, Ngawi Regency.Methods: A case-control study involving 76 pregnant mothers (18-42 years old) from the Pitu Community Health Center area in Ngawi Regency was conducted using purposive sampling. The study needed 38 people per group. This study uses a 1:1 comparison of cases and controls. The modified semi-quantitative food frequency questionnaire was used to collect data on pregnant women’s dietary patterns. Anthropometric data measured MUAC (Upper Arm Circumference) using standard measurements. The obtained data were analyzed by using the Chi-Square test.Results: The similarities in both the case and control groups are that the majority of mothers are of non-risk age for childbirth, have low socioeconomic status, are housewives, and have inadequate iron intake. However, in the case group, inadequate vitamin C intake was also found. There is a significant relationship between nutritional status (p=0.049; OR=0.255) and feeding frequency (p=0.001; OR=5.385) with hemoglobin levels. Type and amount of feedings had no relationship with hemoglobin levels (p=0.818: OR=0.810).Conclusions:  The study reveals an inverse relationship between nutritional status and feeding frequency and hemoglobin levels, but not for the type and amount of feedings among pregnant women at the Pitu District Health Center, Ngawi Regency.